The New Urbanism Principle of Quality Architecture and Urban Design Versus Place Identity. A Case Study of Val D’Europe and the Manufaktura Complex - Cysek-Pawlak, Monika Maria; Krzysztofik, Sylwia (European Spatial Research and Policy, 2018)
This article contributes to the New Urbanism debate by considering the relationship between the identity of a place and quality in architecture and urban design. It combines a general theoretical discussion and an operational analysis with a comparative study of two commercial centres: Manufaktura in Łódź (Poland) and Val d’Europe in Marne-la-Vallée (France). It concludes that while the guidelines of New Urbanism can help both private investors and public stakeholders make better strategic decisions, according to the concept of quality architecture and urban design, its framework should be applied with care for community needs and the historical character of the city.